USE OF PULSE OXIMETRY WITH PLETHYSMOGRAM REGISTRATION IN CHILDREN WITH ACUTE PNEUMONIA - Buriak, Oleksandr; Nechytailo, Yurii (Eastern Ukrainian Medical Journal, 2025)
Introduction. Clinical examination of the patient includes first of all the assessment of heart rate by peripheral pulse. Assessment of pulse rate is simple and can be done manually or with devices such as pulse oximeter which registers pulse waves in photoplethysmogram. Photoplethysmogram provides a means of low-cost physiological monitoring that is popular in many wearable devices but with the accuracy, robustness and useful for clinical studies and healthcare.Materials and Methods. A total of 50 children aged 7 to 12 years were enrolled in the study and divided into two groups: 28 children with acute pneumonia in early recovery stage and 22 healthy children. The cardiovascular parameters were assessed by blood pressure, pulse rate and pulse oximetry with photoplethysmogram pulse wave analysis.Results. The pulse rate was nearly the same in both groups (acute pneumonia patients – 87.6±2.3 bpm and healthy subjects – 85.1±1.9 bpm), but a mean systolic blood pressure in acute pneumonia patients was significantly lower than in the healthy children (103.6±3.1 and 114.7±2.8, p<0.05). Measurements of photoplethysmogram indices in both groups showed no significant differences, with the exception of the dicrotic wave amplitude, which was lower in acute pneumonia patients (0.78±0.29 mm and 1.41±0.39 mm, p<0.05). These changes were assessed as a result of endothelial dysfunction, impaired microcirculation, and higher peripheral resistance to blood flow in patients with acute pneumonia.Conclusions. In addition to assessing blood oxygen saturation, pulse oximetry utilizes photoplethysmography to register pulse waves, providing important information regarding vascular system function. Pulse wave analysis indicates changes at the microcirculatory level and an increase in peripheral resistance to blood flow in children with acute pneumonia.